EDGE: from quiescent to gas-rich to star-forming low-mass dwarf galaxies. Issue 2 (12th August 2020) - Rey, Martin P; Pontzen, Andrew; Agertz, Oscar; Orkney, Matthew D A; Read, Justin I; Rosdahl, Joakim
ABSTRACT: We study how star formation is regulated in low-mass field dwarf galaxies (10^5 M_ 10^6 M_ ), using cosmological high-resolution (3 pc ) hydrodynamical simulations. Cosmic reionization quenches star formation in all our simulated dwarfs, but three galaxies with final dynamical masses of 3 × 10^9 M_ are subsequently able to replenish their interstellar medium by slowly accreting gas. Two of these galaxies reignite and sustain star formation until the present day at an average rate of 10^-5 M_ yr^-1, highly reminiscent of observed low-mass star-forming dwarf irregulars such as Leo T. The resumption of star formation is delayed by several billion years due to residual feedback from stellar winds and Type Ia supernovae; even at z = 0, the third galaxy remains in a temporary equilibrium with a large gas content but without any ongoing star formation. Using the 'genetic modification' approach, we create an alternative mass growth history for this gas-rich quiescent dwarf and show how a small (0.2 dex) increase in dynamical mass can overcome residual stellar feedback, reigniting star formation. The interaction between feedback and mass build-up produces a diversity in the stellar ages and gas content of low-mass dwarfs, which will be probed by combining next-generation H i and imaging surveys.